2012
DOI: 10.3389/fpsyg.2012.00169
|View full text |Cite
|
Sign up to set email alerts
|

Setting Up the Speech Production Network: How Oscillations Contribute to Lateralized Information Routing

Abstract: Speech production involves widely distributed brain regions. This MEG study focuses on the spectro-temporal dynamics that contribute to the setup of this network. In 21 participants performing a cue-target reading paradigm, we analyzed local oscillations during preparation for overt and covert reading in the time-frequency domain and localized sources using beamforming. Network dynamics were studied by comparing different dynamic causal models of beta phase coupling in and between hemispheres. While a broadban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
90
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(107 citation statements)
references
References 37 publications
11
90
1
2
Order By: Relevance
“…Similarly, studying the "regional co-variation" of this network in language processing tasks and tasks of nonverbal executive control should provide valuable information as to the functional (and potentially evolutionary) relationship between the human capacity for language and general reasoning and action. Importantly, this putative relationship brings with it the caveat that the involvement of pFC regions in different speech production tasks may not so much reflect executive processes as tied to speech production per se than to the various contingencies in which speech is elicited (Gherig et al, 2012;Jeon and Friederici, 2013). Future research aiming at disentangling such co-variation will face this methodological problem, necessitating careful construction of its materials and methods, as well as ecologically informed interpretation of the results.…”
Section: Summary and Future Researchmentioning
confidence: 87%
See 2 more Smart Citations
“…Similarly, studying the "regional co-variation" of this network in language processing tasks and tasks of nonverbal executive control should provide valuable information as to the functional (and potentially evolutionary) relationship between the human capacity for language and general reasoning and action. Importantly, this putative relationship brings with it the caveat that the involvement of pFC regions in different speech production tasks may not so much reflect executive processes as tied to speech production per se than to the various contingencies in which speech is elicited (Gherig et al, 2012;Jeon and Friederici, 2013). Future research aiming at disentangling such co-variation will face this methodological problem, necessitating careful construction of its materials and methods, as well as ecologically informed interpretation of the results.…”
Section: Summary and Future Researchmentioning
confidence: 87%
“…3 Notice that several studies have reported activation of anterior pFC regions also in the context of overt sentence reading (Kell et al, 2010;Gherig et al, 2012), possibly downplaying an interpretation of their activity as related to generative speech. Importantly, however, the reading tasks employed in these studies were part of a broader task-switching paradigm likely to call for flexible rule learning -a capacity heavily dependent on the exploratory capacities of the fronto-polar cortex (see Gherig et al, 2012). Anterior frontal activity in these studies may therefore pertain not so much to the speech tasks per se than to the general study paradigm.…”
Section: A Rostro-caudal Axis For Continuous Speech In Pfcmentioning
confidence: 97%
See 1 more Smart Citation
“…Reported activations with a duration equal to or longer than our window length of 1000 ms (e.g. Gehrig, Wibral, Arnold, & Kell, 2012) have been excluded from the figures on the timings of reported activities. Following conventional logic, the timing of activities is critical to understanding how the speech network areas interact, and such long time-windows cannot contribute evidence regarding this issue.…”
Section: Timing Of Identified Activity Contrastsmentioning
confidence: 99%
“…Task cueing paradigms have been successfully applied to investigate the neural processes underlying the intention to speak in monolinguals. For instance, in anticipation of linguistic material for articulation, subjects activate the entire language production network 2-4 s prior to speaking, including the frontopolar (BA 10) and anterior cingulate cortices, the supplementary motor areas (SMAs), and the caudate nuclei (Gehrig, Wibral, Arnold, & Kell, 2012;Kell, Morillon, Kouneiher, & Giraud, 2011). In the case of bilingual language production, it remains unknown whether preparatory processes associated with speech production include representations specific to the language the speaker chooses to speak.…”
Section: Introductionmentioning
confidence: 99%